Grimmia (Grimmiaceae, Bryophyta) in southern Mexico (Oaxaca and Chiapas) - Delgadillo Moya, Claudio; Peña Retes, Ana Paola (Instituto de Ecología, A.C., 2018)
Background and Aims: The taxonomy and distribution of Grimmia are well known because of recent reviews in global, continental, and regional studies. However, collections from some areas like southern Mexico are scarce. This study updates the distribution of Grimmia in southern Mexico and attempts to revise the hypothesis of its geographical distribution.Methods: Field work in Oaxaca and Chiapas complemented records in a Neotropical database of Grimmia. Collections from these states partly validated models of potential distribution for several species prepared in a previous study.Key results: There are three species of Grimmia in southern Mexico: G. longirostris, G. pilifera, and G. trichophylla. The last species is the only record for Chiapas where it is associated with other temperate and subtropical mosses.Conclusions: Its known range in Mexico, as supported by the study of more than 900 specimens from this country, suggests that Grimmia arrived from North America, not from a southern origin because key species have not been found in Oaxaca and Chiapas.